Pengantar editorial MediaPsi 8(2) 2022 - Nurmala, Sukma (Universitas Brawijaya, 2022)
This introductory section summarizes the contributions in this edition of MediaPsi. The first article discusses the benefits of interpersonal psychotherapy in reducing depression. The subsequent paper provides an overview of the development of cognitive function in preschool children during the Covid-19 pandemic. The third article enhances educators' awareness of the importance of developing positive teaching to increase learning effectiveness. The fourth contribution encourages fathers in Indonesia to be more involved in child-rearing. The final contribution discusses how logotherapy can help promote positive self-esteem. Keywords: interpersonal psychotherapy, cognitive functioning, positive teaching, father involvement, logotherapy